2022
DOI: 10.1007/s11920-022-01326-3
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Cognitive Behavioral Treatment for Insomnia on Depression and Anxiety Outcomes

Abstract: Purpose of Review With a focus on reviewing adequately powered randomized controlled trials, we present recent research on the potential of cognitive behavioral therapy for insomnia (CBT-I) to improve depression and anxiety outcomes among patients with insomnia and one of the following comorbid psychiatric disorders: major depressive disorder (MDD), generalized anxiety disorder (GAD), or posttraumatic stress disorder (PTSD). We also examine potential moderators of CBT-I on depression and anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 65 publications
(85 reference statements)
2
26
0
Order By: Relevance
“…Not all studies have demonstrated CBT-I superior to control on reducing depressive symptoms, however (e.g., Carney et al, 2017 ; Manber et al, 2016 ). A review of key moderators of the impact of CBT-I on depression and anxiety highlights two additional possible explanations for our null findings (Mirchandaney et al, 2022 ). First, individuals with evening circadian preferences appear to benefit most from CBT-I on comorbid psychological symptoms like depression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Not all studies have demonstrated CBT-I superior to control on reducing depressive symptoms, however (e.g., Carney et al, 2017 ; Manber et al, 2016 ). A review of key moderators of the impact of CBT-I on depression and anxiety highlights two additional possible explanations for our null findings (Mirchandaney et al, 2022 ). First, individuals with evening circadian preferences appear to benefit most from CBT-I on comorbid psychological symptoms like depression.…”
Section: Discussionmentioning
confidence: 81%
“…Cognitive behavioral therapy for insomnia (CBT-I) is the recommended treatment for insomnia (Schutte-Rodin et al, 2008 ) and has also demonstrated treatment benefits on reduced symptoms of depression (Christensen et al, 2016 ; Suh, 2015 ; Thorndike et al, 2013 ) and anxiety (Jansson-Fröjmark & Norell-Clarke, 2016 ; Thorndike et al, 2013 ). Moreover, while there is some mixed evidence on this point (Mirchandaney et al, 2022 ), the benefits of CBT-I on the symptoms of depression and anxiety appear greatest among those entering treatment with higher initial symptomatology (Blake et al, 2018 ; Lancee et al, 2013 ; Sandlund & Norell-Clarke, 2020 ). Addressing insomnia with CBT-I among older adults may therefore help address comorbid symptoms of depression and anxiety.…”
mentioning
confidence: 99%
“…Despite this frequent co-occurrence and bidirectional relationship, insomnia requires targeted intervention, such as CBT-I, to evidence improvements. Indeed, CBT-I is superior to anxiety-focused treatment in improving insomnia symptoms among those with comorbid anxiety disorders and shows moderate to large effects in reducing comorbid anxiety symptoms ( 67 , 68 ). However, up to 30% of individuals with comorbid anxiety do not experience insomnia-related benefit from CBT-I ( 69 ), suggesting that additional intervention components may be needed to mitigate co-occurring anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological treatments include cognitive behavioral therapy for insomnia (CBT-I). Although CBT-I is currently considered the most effective non-pharmacological treatment for insomnia, CBT-I has sleep restriction and other demanding treatments ( 16 ). The treatment may be the factor in the stress experienced by patients during CBT-I, directly or indirectly leading to increased anxiety and depressive symptoms during treatment ( 17 ).…”
Section: Introductionmentioning
confidence: 99%